Fair and Welfare-Consistent Global Income Poverty Measurement : Theory and Application - Decerf, Benoit; Ferrando, Mery; Quinn, Natalie N. (World Bank, Washington, DC, 2021)
There is growing support for the idea that global income poverty should be assessed with a measure accounting for both own income and relative income. The trade-off that such a measure makes between own income and relative income is the key question. Non-paternalism requires that this trade-off be welfareconsistent, that is, related to individual preferences. This paper studies the implications of requiring that the poverty measure makes a fair and welfare-consistent aggregation of individual preferences. The results provide support for the absolute and relative global lines proposed in the literature but rule out the use of classical poverty indexes. In particular, the paper finds that the ubiquitoushead-count ratio violates a minimal welfare-consistency property. The paper shows empirically that using a modification of the head-count ratio that satisfies this property has major implications for the evaluation of global poverty.